Effects of political institutions on the external debt-economic growth nexus in Africa - Yann Nounamo; Simplice Asongu; Henri Njangang Ndieupa; Sosson Tadadjeu (African Governance and Development Institute (AGDI), 2021)
The main contribution of this study is the determination of an endogenous threshold of institutional quality, beyond which external debt would affect economic growth differently. The focus is on 14 countries of the African Franc zone over the period 1985-2015. Based on the panel Smooth Threshold Regression model, the results reveal that the relationship between external debt and economic growth is based on institutional quality. It is found that the level of indebtedness at which the effect of external debt on economic growth becomes negative is higher in countries with lower levels of corruption and high levels of democracy. This means that poor institutional quality prevents a country from taking full advantage of its credit opportunities. Thus, the more countries become democratic, the more debt helps finance economic growth. These results are robust to sensitivity analysis and Generalized Method of Moments estimation.
Keywords: 330; external debt; political institutions; economic growth